2010
DOI: 10.1007/s12350-009-9164-z
|View full text |Cite
|
Sign up to set email alerts
|

11C-meta-hydroxyephedrine defects persist despite functional improvement in hibernating myocardium

Abstract: Background-Regional cardiac sympathetic nerve dysfunction develops in hibernating myocardium and may play a role in its association with sudden cardiac death. Interventions to improve cardiac function (i.e., revascularization) improve survival, but the potential reversibility of sympathetic nerve dysfunction remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
(82 reference statements)
2
11
0
1
Order By: Relevance
“…The regional 11 C-HED uptake defect (arrows) with preserved 18 F-FDG uptake is seen only after ischemia. The defect in 11 C-HED uptake at 1 week is reduced at 2 months 11 C-HED PET [26]. In human hearts, slow (after >18 months) but progressive reinnervation has been shown by various approaches including PET imaging in patients after heart transplantation [27].…”
Section: Discussionmentioning
confidence: 99%
“…The regional 11 C-HED uptake defect (arrows) with preserved 18 F-FDG uptake is seen only after ischemia. The defect in 11 C-HED uptake at 1 week is reduced at 2 months 11 C-HED PET [26]. In human hearts, slow (after >18 months) but progressive reinnervation has been shown by various approaches including PET imaging in patients after heart transplantation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, due to the non-invasive technique of these imaging tools, their model and imaging approach can provide a means to evaluate the progression of HF and to quantify the temporal changes in flow and metabolism. In addition to the information provided on perfusion and metabolic outcomes, additional imaging could be applied to interrogate regional activation of critical receptors or enzymes within the myocardium, [24][25][26][27][28] neurohormonal changes, [29][30][31][32][33] along with regional changes in myocardial hypoxia, 34 apoptosis, 35,36 necrosis, 37 and fibrosis. 38 Unfortunately, the current study reported a high attrition (overall survival rate of 26%) with a major cause of death attributable to lethal arrhythmias during the perioperative period.…”
Section: See Related Article Pp 655-665mentioning
confidence: 99%
“…31 13 NH3 also offers good accuracy for measuring absolute myocardial blood flow (MBF), but is less practical than 82 Rb because it requires a cyclotron. 18 F-flurpiridaz is a novel radiotracer that is currently undergoing evaluation in a Phase 3 trial. Given that it is an 18 F labeled compound, a cyclotron is required for production.…”
Section: Rationale Of Petmentioning
confidence: 99%
“…Given that it is an 18 F labeled compound, a cyclotron is required for production. 18 Fflurpiridaz has a longer half-life of 110 min, which affords the option of centralized production and distribution to individual centers within close proximity. Moreover, 18 F-flurpiridaz is also suitable for exercise stress testing; has superior spatial resolution because of its very short positron range, as well as high first-pass extraction even at increased flow rates, rendering it ideal for flow quantification.…”
Section: Rationale Of Petmentioning
confidence: 99%
See 1 more Smart Citation